DEVELOPMENT OF SOFTWARE SYSTEM FOR MONITORING OF STRESS CORROSION CRACKING OF THE PIPELINE UNDER TENSION - Z. K. Abaev; B. A. Bachiev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The software and hardware development tendency, providing the automated monitoring and control of basic and auxiliary technological processes of gas transportation via system of main gas pipelines has been revealed. The article discusses the stages of creation of the software of system of monitoring corrosion cracking under tension (SCC). The new useful adequate regression models development determining the risk level of LCC is shown. A ranking sections algorithm of main gas pipeline (MG) on the propensity to SCC is presented. Adequate developed regression equation determining the LCC risk level has been developed. To count the main gas pipeline lifetime the variable rank of the danger of SCC (RSCC) on the basis of methods of fuzzy logic is proposed to use. Implementation of the fuzzy model was carried out using the graphical tools developed in MATLAB using the expansion pack Fuzzy Logic Toolbox. The working algorithm of developed program and the screen forms are presented.